Noise reduction via optimal control in a light-matter quantum system - Francisco Albarrán-Arriagada; Guillermo Romero; Enrique Solano; Juan Carlos Retamal (Physical Review Research)
Quantum noise reduction below the shot-noise limit is a signature of light-matter quantum interaction. A limited amount of squeezing can be obtained along the transient evolution of a two-level system resonantly interacting with a harmonic mode. We propose the use of optimal quantum control over the two-level system to enhance the transient noise reduction in the bosonic mode in a system described by the Jaynes-Cummings model. Specifically, we propose the use of a sequence of Gaussian pulses in a time window where the dissipative effects are negligible. We find that the correct choice of pulse times can reduce the noise in the quadrature field mode well below the shot noise, reaching reductions of over 80%. As the Jaynes-Cummings model describes a pivotal light-matter quantum system, our approach for noise reduction provides an experimentally feasible protocol to produce a nontrivial amount of squeezing with current technology.